Does prey scarcity increase the risk of wolf attacks on domestic dogs? ... - Kojola, Ilpo; Hallikainen, Ville; Kübarsepp; Männil, Peep; Tikkunen, Mari; Heikkinen, Samuli (Dryad, 2022)
Gray wolf (Canis lupus) predation on domestic dogs (Canis familiaris) is a considerable wolf-human conflict issue in several regions of Europe and North America but has not been well documented in the scientific literature. Livestock depredations by wolves may be related to the abundance of wild prey. Regardless of the presumed motivations of wolves for attacking dogs (likely due to interference competition and predation), the abundance of wild prey populations may also influence the risk of wolf attacks on dogs. We examined whether the annual number of tatal attacks by wolves on dogs was related to the abundance of primary prey, including wild boar (Sus scrofa) and roe deer (Capreolus capreolus) in Estonia, as well as the abundance of moose (Alces alces) in Finland. Statistical models resulted in significant negative relationships, thus providing evidence that the risk of attacks in both house yards (Estonia) and hunting situations (Finland) was highest when the density of wild prey was low. Wild ungulates ... : The regional number of wolf packs is annually estimated as a part of Finnish and Estonian wolf monitoring programs. Finnish hunters estimate the post-hunt moose population by moose management zones providing publicly available data. By adding the official number of moose harvested to the post-hunt estimate we pre-hunt estimates. The number of dog hunting days in moose hunting is recorded by moose hunting clubs. In Estonia the official records for the annual numbers of roe deer and wild boar harvested in each province were used as proxies of population densities. State authorities keep records with geographic position of dogs killed by wolves. ...